Assessment of information communication technology proficiency of secondary school teachers - Osaheni Oni; Kelly Odaro-Ekhaguebor; Emmanuel Akpoduado (Journal of Pedagogical Research, 2018)
This study assessed Information and Communication Technology (ICT) Proficiency of Secondary School Teachers in Auchi Polytechnic Staff School.  The study employed a descriptive surveyed design and purposive sampling techniques to select fifty-three (53) respondents for the study.  A structured questionnaire was used to collect data. The data collected were analyzed and presented in frequency distribution tables.  The results of the study show that majority of the teachers in the staff school do not use Information and Communication Technology as pedagogy for teaching.  The teachers also have negative attitude towards Information and Communication Technology.  Lack of ICT policy in secondary school, epileptic power supply, lack of regular and adequate training, lack of technical support from government and private sector, hardware and software problems and poor network/Bandwidth are some of the challenges militating against teachers' readiness and effective use of Information and Communication Technology for teaching. The study therefore recommends that Government should be committed to full implementation of ICT in secondary schools by providing the necessary infrastructure, equipment; formulate policies and implementing the existing one if any.